Developing Intercultural Communicative Competence in Vocational Foreign Language Courses: Case Study of Japanese and Korean Learners - Djafri, Fatmawati; Hasanah, Ummul (Universitas Negeri Semarang, 2025)
The 21st Century Skills Framework identifies foreign language proficiency and intercultural communication as core competencies essential for individuals’ future lives and careers. In response, higher education institutions have increasingly emphasized the development of graduates equipped with strong communication abilities and intercultural understanding to meet the demands of the global labor marker. Beyond linguistic competence, a deep understanding of the cultural contexts and communication patterns inherent in the target languages –such as Japanese and Korean—is critical. This study aims to explore and analyze the perspectives of university students learning Japanese and Korean regarding the communication styles and cultural backgrounds embedded in these languages. Employing a mixed-methods approach, the study collected quantitative data through questionnaires distributed to students enrolled in “Introduction to Communication” (Japanese) and Korean language courses. Qualitative data were gathered through focus group discussions and student essays on intercultural communication, conducted as part of the classroom activities. The findings reveal that students develop intercultural communicative competence by integrating cognitive, affective, and behavioral dimensions, fostered through reflective learning practices in both language courses.